How long can this party last? What the rise and fall of OR/MS can teach us about the future of business analytics. Issue 5 (3rd September 2019) - Otondo, Robert F.
ABSTRACT: Business analytics (BA) is an important organisational activity and research discipline. However, history has shown that information systems (IS)-related disciplines with promising futures do not always flourish as expected. The troubled history of one such discipline (i.e., operations research/management science, or OR/MS) serves as a cautionary tale for the BA community because it warns of the dangers of an unquestioning faith in the power of mathematical modelling and analysis. This cautionary tale is especially alarming given the methodological similarities between BA and OR/MS, as well as the sizeable investments organisations have made in their BA capabilities. It is, therefore, appropriate and prudent to ask if a similar fate could befall BA and how such a fate can be avoided. Those questions are addressed in this article by extracting "lessons learned" from the OR/MS literature and applying them to BA. The lessons highlight opportunities and challenges to BA which are then framed within a widely cited research agenda. Theoretical propositions are forwarded to encourage research that can help promote the future of BA – both as an organisational practice and research stream – through a wider, broad-based, and balanced critical discourse among scholars and practitioners.